1997
DOI: 10.1159/000190267
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Ambulatory Peritoneal Dialysis in Patients after Infra-Abdominal Prosthetic Vascular Graft Surgery

Abstract: The purpose of this study was to assess the feasibility of continuous ambulatory peritoneal dialysis (CAPD) after intra-abdominal prosthetic vascular graft surgery. We report 8 consecutive patients with end-stage renal disease, who previously underwent intra-abdominal prosthetic aortic graft replacement, treated by CAPD between November 1983 and November 1994. All patients received a peritoneal dialysis catheter without technical problems and were dialyzed for a total of 208 months. Six episodes of peritonitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, the use of PD may offer considerable advantages in these patients including better hemodynamic control and avoidance of anti-coagulation. There have been three retrospective reviews that have shown no significant risk in using PD in patients with past history of open abdominal aortic aneurysm (AAA) repair [39][40][41]. In fact, in one study of 8 patients revealed that there were six episodes of peritonitis without clinical evidence of graft infection [39].…”
Section: Intra Abdominal Foreign Bodymentioning
confidence: 99%
“…However, the use of PD may offer considerable advantages in these patients including better hemodynamic control and avoidance of anti-coagulation. There have been three retrospective reviews that have shown no significant risk in using PD in patients with past history of open abdominal aortic aneurysm (AAA) repair [39][40][41]. In fact, in one study of 8 patients revealed that there were six episodes of peritonitis without clinical evidence of graft infection [39].…”
Section: Intra Abdominal Foreign Bodymentioning
confidence: 99%